Lesson Learn The Leadership Period of Admiral Keumalahayati for the Development of Maritime Defense Strategy - Anis Nur Laily; Agus Adriyanto; Lukman Yudho Prakoso (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Aceh is one of the provinces in Indonesia which is located at the tip of Sumatra Island. History records that Aceh has a strategic position which is the starting point for trade from the sea. Both national and international traders use Aceh as a transportation route. The maritime history of the Kingdom of Aceh can be preserved and published, such as the story of Admiral Keumalahayati. The purpose of this research is to take lessons from the story of Admiral Keumalahayati's leadership for the development of a maritime defense strategy. This study uses qualitative methods and uses a socio-political approach to determine the character of leadership and historical methods to determine the journey of Admiral Keumalahayati's leadership. The results showed that Admiral Keumalahayati had been the leader of the Inong Bale Troop (widow woman), conducting diplomacy with countries that wanted to cooperate with the Kingdom of Aceh. Admiral Keumalahayati was the first female warlord to become the navy leader of the Kingdom of Aceh. This maritime history ultimately has a significant role in overcoming several problems related to Indonesia's position as the world's maritime axis country.